Water-soluble oligofluorenes bearing N1-alkylcytosine side chains as turn-on and turn-off materials in telomere DNA length sensing. Issue 74 (17th August 2020) - Yamaguchi, Isao; Ooe, Ryoga; Wang, Aohan
Abstract : Soft materials for telomere DNA length sensing were developed. Abstract : Water-soluble cationic and anionic oligofluorenes bearing N 1 -alkylcytosine side chains, namely OF-1 and OF-2, were synthesized. The photoluminescence (PL) intensity of an aqueous solution of OF-1 decreased on the addition of (TTAGGG) m as telomere DNA models. In contrast, the PL intensity of OF-2 increased on the addition of DNA.